A Critical Discourse Analysis of West Kalimantan Folktales Using Norman Fairclough’s Three-Dimensional Model - Muhammad Nurul Asa (Universitas Negeri Semarang, 2025)
This study applies Fairclough’s Critical Discourse Analysis to uncover ideologies embedded in the language of West Kalimantan folktales, explaining why these stories remain relevant for education, cultural events, and community life. Nine well-known folktales were analyzed. At the textual level, the tales reveal dominant lexical fields distinguishing Malay and Dayak traditions. Moral and punishment lexis appear across all stories, with metaphorical transformations (stone, bird, flood, mountain) symbolizing consequences for good and bad deeds. Malay tales focus on family and social conflicts, while Dayak tales emphasize ecological violations. At the discursive practice level, the stories exist in oral, written, digital, and institutional forms with varied audiences. Distribution tends toward standardized written Indonesian that highlights morality and belief, while interpretations remain diverse yet consistently stress moral lessons. At the sociocultural level, two ideological notions persist: morality as harmony and belief in supernatural authority. Malay tales promote social-centered morality under a dual human-God cosmology, while Dayak tales highlight ecological morality within a tripartite cosmology of humans, nature, and spirits. These folktales endure by continuously reproducing the sense that being Malay or Dayak means living within a moral universe governed by higher authority and shared values.